2015
DOI: 10.1063/1.4918341
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic and optical properties of Sn1−xZnxO2 nanoparticles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In particular, we identify that for the more strongly ferromagnetic compositions the nanoparticles have regular shaped structures with nanoneedles on their surfaces where the (110) and (101) planes are present. This is particularly signicant in the sense that calculations 21 have shown that ferromagnetic defects (V Sn ) are energetically favoured on these surfaces. Hence there appears to be a correlation between the morphological structure and ferromagnetic behaviour via the anisotropic growth of nanostructures with surfaces that stabilize ferromagnetic defects.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, we identify that for the more strongly ferromagnetic compositions the nanoparticles have regular shaped structures with nanoneedles on their surfaces where the (110) and (101) planes are present. This is particularly signicant in the sense that calculations 21 have shown that ferromagnetic defects (V Sn ) are energetically favoured on these surfaces. Hence there appears to be a correlation between the morphological structure and ferromagnetic behaviour via the anisotropic growth of nanostructures with surfaces that stabilize ferromagnetic defects.…”
Section: Discussionmentioning
confidence: 94%
“…Fig. 6(c) displays the Zn 2p core level region where the Zn 2p 3/2 peak appears at a binding energy of 1021.1 eV, 21,46 con-rming that Zn atoms were incorporated into the Sn lattice and form Zn-O bonds. We analysed at least three different spots on every sample and found that the Zn concentration did not vary between different spots, which indicates that the Zn concentration in these samples is homogeneously distributed.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental doping has been reported as an effective strategy for ameliorating the semiconductor photocatalysts; , besides its easy preparation for adjusting the optical band gap structure, it can also generate more active sites via the lattice optimization, including S-doping, P-doping, or N-doping, etc. Zhang et al constructed a new type of P-doped MoS 2 /g-C 3 N 4 composite to effectively enhance the catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Doped tin oxide is used for solar cells [1], gas sensor [2], photo catalysis [3], pollutants detection [4], anode for ion lithium batteries [5] as quantum dots [6,7], ferromagnetic [8] and photoconductive devices. Nowadays, Zn doped SnO2 show promising applications for high temperature semiconductor [9] and optoelectronics devices [10], both properties are being improved by tuning the amount and type of dopants. In solar energy research, Zn doped SnO2 nanoparticles (NPs) are being used as photo anode material to induce negative shift in the flat-band potential to increase the isoelectric point in dye-sensitized solar cell [11].…”
Section: Introductionmentioning
confidence: 99%